2021
DOI: 10.34172/jrhs.2021.64
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Met and Unmet Care Needs in Older Adults without Mental Disorders Using the Camberwell Assessment of Need for the Elderly: A Systematic Review and Meta-analysis

Abstract: Background: Physical, psychological, and social changes in the aging lead to new needs in the care of the elderly. The Camberwell Assessment of Need for the Elderly (CANE) evaluates older adults' care needs. This study aimed to assess the types of needs of the elderly using the CANE questionnaire. Study design: A systematic review. Methods: This systematic review included all cross-sectional studies. International databases, including Web of Sciences, Medline, Scopus, and ProQuest were searched up to June 2021… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…CANE is a versatile tool that can be adapted to different cultural contexts and has been used in various countries to assess the needs of the elderly population. It helps in identifying unmet needs and planning appropriate interventions and support for both elderly individuals and their caregivers 20 . The instrument comprises 24 items spanning four domains: environmental, physical, psychological, and social needs, with two additional items assessing PWLD needs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CANE is a versatile tool that can be adapted to different cultural contexts and has been used in various countries to assess the needs of the elderly population. It helps in identifying unmet needs and planning appropriate interventions and support for both elderly individuals and their caregivers 20 . The instrument comprises 24 items spanning four domains: environmental, physical, psychological, and social needs, with two additional items assessing PWLD needs.…”
Section: Methodsmentioning
confidence: 99%
“…It helps in identifying unmet needs and planning appropriate interventions and support for both elderly individuals and their caregivers. 20 The instrument comprises 24 items spanning four domains: environmental, physical, psychological, and social needs, with two additional items assessing PWLD needs. In this study, caregivers completed the questionnaire to express their perspectives on their care recipients' needs, ensuring a comprehensive assessment without overburdening patients or caregivers.…”
Section: Care Needs Measurementmentioning
confidence: 99%
“…Vytvorený prehľad zahŕňa nástroje, ktorých schopnosť zachytiť možné nedostatky a teda nenaplnené potreby bola skúmaná v rôznom prostredí (komunitné zariadenia, nemocnice, starostlivosť v domácom prostredí, denné stacionáre, väznica) a na rôznom výskumnom súbore pacientov, teda aj u pacientov s diagnostikovanými rôznymi ochoreniami, či iným zdravotným postihnutím. Identifikované nástroje hrajú kľúčovú úlohu pri identifikácii potrieb jednotlivých pacientov a prispievajú k zlepšeniu kvality poskytovanej starostlivosti (Cheraghi et al, 2021). Nástroj InterRAI AC sa zameriava na efektívne posúdenie funkčných a psychosociálnych problémov, geriatrických syndrómov a identifikáciu pacientov vyžadujúcich komplexné vyšetrenie (Boscart et al, 2021).…”
Section: Diskusiaunclassified
“…The specific needs of older adults must be met to promote active aging, including physical, psychological, social, environmental, care and health-related needs (27,28). Ashokkumar et al (29) indicated that older adults had unmet needs such as adaptation to the living environment, hearing and vision problems, income, daily activities, physical diseases, close association, and self-care, while their therapeutic and medicinal needs were met by the caregivers (29).…”
Section: Introductionmentioning
confidence: 99%
“…These studies focused on quantitative methods (cross-sectional) and were carried out in Iran, Brazil, Germany, Thailand, Poland, the Netherlands, and England in 2000-2020. The Camberwell Assessment of Need for the Elderly (CANE) was used to assess met and unmet care needs (27). Qualitative studies can specify people's views and experiences more precisely than quantitative research because they enable participants to express themselves while providing data (12).…”
Section: Introductionmentioning
confidence: 99%